Endophytic Fungi Activated Similar Defense Strategies of Achnatherum sibiricum Host to Different Trophic Types of Pathogens - Shi, Xinjian; Qin, Tianzi; Liu, Hui; Wu, Man; Li, Juanjuan; Shi, Yansong; Gao, Yubao; Ren, Anzhi (Frontiers in Microbiology, 2020)
It is well documented that Epichloë endophytes can enhance the resistance of grasses to herbivory. However, reports on resistance to pathogenic fungi are limited, and their conclusions are variable. In this study, we chose pathogenic fungi with different trophic types, namely, the biotrophic pathogen Erysiphales sp. and the necrotrophic pathogen Curvularia lunata, to test the effects of Epichloë on the pathogen resistance of Achnatherum sibiricum. The results showed that, compared to Erysiphales sp., C. lunata caused a higher degree of damage and lower photochemical efficiency (Fv/Fm) in endophyte‐free (E‐) leaves. Endophytes significantly alleviated the damage caused by these two pathogens. The leaf damaged area and Fv/Fm of endophyte‐infected (E+) leaves were similar between the two pathogen treatments, indicating that the beneficial effects of endophytes were more significant when hosts were exposed to C. lunata than when they were exposed to Erysiphales sp. We found that A. sibiricum initiated jasmonic acid (JA)‐related pathways to resist C. lunata but salicylic acid (SA)‐related pathways to resist Erysiphales sp. Endophytic fungi had no effect on the content of SA but increased the content of JA and total phenolic compounds, which suggest that endophyte infection might enhance the resistance of A. sibiricum to these two different trophic types of pathogens through similar pathways.